Help Us Embrace Sustainability by Forgoing Print. Issue 4 (1st October 2017) - Baker, Gary
Abstract : We currently print and ship over 100 metric tons of paper a year to members worldwide in the form of hard copies of the Financial Analysts Journal, which goes against the formal sustainability mission of CFA Institute to use resources responsibly and achieve its objectives ethically. What can you do to help? If possible, go digital and forgo print!